Heterologous prime-boost oral immunization with GK-1 peptide from Taenia crassiceps cysticerci induces protective immunity - Fragoso, Gladis (2011)
Oral immunization is a goal in vaccine development, particularly for pathogens that enter the host through the mucosal system. This study was designed to explore the immunogenic properties of the Taenia crassiceps protective peptide GK-1 administered orally. Mice were orally immunized with the synthetic GK-1 peptide in its linear form with or without the Brucella lumazine synthase (BLS) protein adjuvant or as a chimera recombinantly bound to BLS (BLS-GK-1). Mice were boosted twice with GK-1 only at 15-day intervals. A significant rate of protection of 64.7% was achieved in GK-1-immunized mice, and that rate significantly increased to 91.8 and 96% when mice were primed with GK-1 coadministered with BLS as an adjuvant and BLS as a carrier, respectively. Specific antibodies and T cell activation and proliferation accompanied the protection induced, revealing the potent immunogenicity of GK-1. Through immunohistochemical studies, GK-1 was detected in T and B cell zones of the Peyer's patches (PP) and mesenteric lymph nodes. In the latter, abundant proliferating cells were detected by 5'-bromo-2'-deoxyuridine incorporation. No proliferation was detected in PP. Altogether, these results portray the potent immunogenic properties of GK-1 administered orally and reinforce the usefulness of BLS as an adjuvant and adequate vaccine delivery system for oral vaccines.